Ailments, ilness and sufferings in woman through painting - Villaverde Solar, Mª Dolores (Revista Internacional de Ciencias Podológicas, 2010)
In art from antiquity was sought beauty perfect, because it deformed disagrees with the definition of art: the ability of man to create beautiful things. This article will examine a series of pictures used to verify not only the role of women in modern and contemporary painting, but also the disabled in the art when it identifies with a lady, and its “use” sometimes to accentuate the drama.